A brief analysis of morphology and terminology for the genus Ablabesmyia (Tanypodinae) - Paggi, Analía Constancia (2009)
The genus Ablabesmyia is well represented in both the north and south Americas, though the latter region is inadequately studied. A few months ago, the authors of this note made contact to exchange type material and literature on the known species of Ablabesmyia from South America. Almost immediately, we faced the problem that we were referring to the same structures by different names, so we decided to sort and organize the different terminologies used along with the most important bibliography of this genus. Furthermore, we wanted to share the misunderstandings we faced with others who want to study Ablabesmyia so they can learn from our mistakes.